Fungal Infection of Pelvis : an Uncommon Cause for Low Backache - Jha, Daman Kumar; Lakhey, Shishir; Rana, Raj; Chitrakar, Niva; Thakur, Jitendra; Poudel, Amit (Nepal Orthopaedic Association Journal, 2023)
This study reports a case of 43 years male with low back ache which on investigation proved to be due to cryptococcus fungal infection of ilium which is an uncommon cause of low backache. The focus of infection was evacuated, and the bone debrided along with administration of anti-fungal drugs. On follow up of 9 months after surgery and antifungal treatment, the patient had no symptoms and there was regression in size of the lesion in the left iliac bone.